(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
The magnetic properties and electronic states of the transition metal doped III-V wurtzite compounds (A1−xMx)N are calculated using Korringa-Kohn-Rostoker Green’s function method combined with the coherent potential approximation, where A = Al, Ga and M = 3d transition metal atoms namely V, Cr, Mn, Fe, Co, Ni and x is the fractional concentration of M. The positive value of the energy difference between ferromagnetic (FM) state and disordered local magnetic moment (DLM) state per unit cell denotes the magnetic phase stability. The total energy difference (EDLMEFM) is used to estimate the Curie temperature (TC) within the mean-field approximation. The calculated TC of V and Cr doped nitrides increases rapidly at lower concentrations and is found to be above the room temperature in the concentration range of x = 0.05 – 0.20. The FM behavior in Mn doped (Al1−xMnx)N is suppressed at the concentration range of x = 0.01 – 0.10. A clear phase transition from DLM to FM state occurs at concentrations x > 0.10. The energy difference in Fe, Co and Ni doped materials, results in lower values of the DLM states, where the super-exchange interaction dominates over the FM one. The FM materials exhibiting TC above room temperature have applications in the field of spintronics. Journal of Bangladesh Academy of Sciences, Vol. 41, No. 2, 217-225, 2017